2016
DOI: 10.4049/jimmunol.1600250
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor HIF-1α Controls Expression of the Cytokine IL-22 in CD4 T Cells

Abstract: IL-22 is expressed by activated lymphocytes and is important in modulation of tissue responses during inflammation. The cytokine induces proliferative and antiapoptotic pathways in epithelial cells allowing enhanced cell survival. This can have positive effects, such as in the maintenance of epithelial barriers in the gastrointestinal tract, but also negative effects, such as contributing to colorectal tumorigenesis. Because IL-22 can be dual-natured, we hypothesized that its biological activity should be tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…In addition, the novel finding that IL-22 is a transcriptional target for HIF may indicate that hypoxia and hypoxiaresponses are globally important in regulating mucosal cytokine responses 39 Given that IL-22 has a dual nature in promoting both inflammation and resolution, contextually coupling both IL-12p40 and IL-22 to a hypoxia response would support the hypothesis that HIF signaling acts to limit the extent of the immune response. Future studies identifying contrasting regulation of HIF/IL-12/23 responses in innate vs. adaptive cells, are likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the novel finding that IL-22 is a transcriptional target for HIF may indicate that hypoxia and hypoxiaresponses are globally important in regulating mucosal cytokine responses 39 Given that IL-22 has a dual nature in promoting both inflammation and resolution, contextually coupling both IL-12p40 and IL-22 to a hypoxia response would support the hypothesis that HIF signaling acts to limit the extent of the immune response. Future studies identifying contrasting regulation of HIF/IL-12/23 responses in innate vs. adaptive cells, are likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HIF1α in inducing cytokine production has been shown in a few reports, such as that of Jeong et al [50] whereby HIF1α inhibition abrogated the deferoxamine-induced cytokine production (IL6, IL8 and TNFα) in human mast cells, HMC-1 cells. Further, Budda et al [51] demonstrated that HIF-1α controlled IL-22 expression in CD4 T Cells under hypoxia. However, the exact mechanism by which HIF1α controls the production of these inflammatory mediators was not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed that in vitro infection with influenza H1N1 virus promotes the secretion of proinflammatory cytokines by inducing nuclear translocation of HIF‐1α (Guo et al., ). HIF‐1α appears to control expression of IL‐22 in CD4 T cells (Budda, Girton, Henderson, & Zenewicz, ). It is also important to stress that changes in secretion of cytokines and chemokines by astrocytes in this study were induced in the absence of any other cells of the NVU from the cultures; this finding is significant because it has been shown previously that tumor necrosis factor like weak inducer of apoptosis is secreted mainly by neurons during CI and binds to Fn14 on astrocytes, leading to proinflammatory molecule production (Saas et al., ).…”
Section: Discussionmentioning
confidence: 99%